Clinical Study on the Influence of Eye Care Habits on Myopia in School-age Children - Meihong, Zhu; Tainan, Lin (E3S web of conferences, 2021)
In order to explore the relationship between the habit of using eyes and myopia, summarize and put forward to develop good habit of using eyes of school-age children to achieve the purpose of preventing myopia. 960 school-age children aged 7 to 12 were selected from the ophthalmology clinic of Fujian Provincial Government Hospital. The data collected included reading distance, sleep time, average daily outdoor activity time, average daily continuous eye use time. Ophthalmologists are responsible for visual examination, which includes mild myopia, moderate myopia and severe myopia. SPSS 22.0 statistical software was used for data processing. As a results, P < 0.05 was statistically significant. There are significant differences in the distribution of sleep time among the three groups (P < 0.05); There are significant differences in the time distribution of each continuous close eye use among the three groups (P < 0.05); There are significant differences in the distribution of distance habit among the three groups (P < 0.05); There are significant differences in the distribution of outdoor activity time among the three groups (P < 0.05).Myopia is closely related to the time of close eye use, the distance of eye use, the length of sleep and the length of outdoor activities.